The effects of monitoring the abundance and species composition of aphids as virus vectors on seed potato production in Serbia - Milošević, Drago M; Milenković, Slobodan; Perić, Pantelija; Stamenković, Svetomir (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
Aphids are the most important vectors of potato viruses during the crop’s growing season. The most widespread and damaging viruses, the potato virus Y and potato leaf roll virus, are transmitted by aphids in non-persistent and persistent manner, respectively. The two viruses cause the greatest concern of potato producers and a great constraint to seed potato production in Serbia, the region and across the world. Potato virus Y is particularly harmful, given its distribution and spreading rate. Seed potato production systems under well-managed conditions involve a series of virus control measures, including the monitoring of outbreaks of winged aphids, their abundance and species composition, in order to forecast virosis, i.e. potential plant and tuber infection periods. Monitoring the aphid vectors of potato viruses enables determination of optimum dates for haulm destruction when higher than normal numbers of winged aphids as vectors of economically harmful diseases have been observed. Haulm destruction in a potato crop reduces the risk of plant infection and virus translocation from the aboveground parts to tubers, thus keeping the proportion of infected tubers within tolerance limits allowed for certain categories of seed potatoes. This practice has positive effects if used in combination with other viral disease control measures; otherwise, it becomes ineffective. This paper provides an integral analysis of the effects and role of monitoring outbreaks of aphids, their abundance and species composition in timing haulm growth termination to prevent plant infection, virus translocation and tuber infestation in potato crops in Serbia and the wider region.
Keywords: Potatoes; Plant viruses; Vectors; Aphids